O papel do poder judiciário sob a perspectiva do Estado Democrático de Direito - Lira, Gabriel Ciríaco (2008)
In Brazil, after the Constitution of 1988 was enacted, we have the increasing of judicial branch activities. These growing of his activities can be tributed to more constiency of citizenship. Brazilian people came each more often to the Courts. It must be recalled that brazilian Judiciary branch is very conservative. Many times judges argued that the have no competency to decide, and these results in a non liquet decision itself. By the other side, we faced a society who officials arrived to their positions as we have been at monarchy system, by inheritage. Judiciary branch must be changed by those who have the judiciary skills lawyers, judges, procecuters, - law actors-. It is not easy change mentalities. Since French Revolution, the law search for legality, who is misunderstanding as legal security. Legality today have constitutional sources. Judicial branch have this important duty beyond the rule of law. Separation of powers was an important theory to stop dictators and ditactorships. However, these theory cannot be applied in Brazil as it was in France, or in any other country. Each people, each Nation, has their own different historic reality who has different remedies and solutions. This dissertation aims to contribute how must be the role of Judicial branch, his mission under constitutional system. Any construction of constitutional system must considered the view of rule of law